2017
DOI: 10.7150/jca.18124
|View full text |Cite
|
Sign up to set email alerts
|

Is pretreatment Epstein-Barr virus DNA still associated with 6-year survival outcomes in locoregionally advanced nasopharyngeal carcinoma?

Abstract: Purpose: The objective of this study was to confirm the association between pretreatment Epstein-Barr virus (EBV) DNA (pre-DNA) load and survival outcomes after long-term follow-up in patients with locoregionally advanced nasopharyngeal carcinoma (LA-NPC).Materials and Methods: Between November 2009 and February 2012, a total of 1036 patients with LA-NPC were enrolled. There were 762 patients in stage III and 274 in stage IVA-B. All patients were treated with radical radiotherapy with or without chemotherapy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 27 publications
(30 reference statements)
1
24
0
Order By: Relevance
“…EBV is a particularly sensitive indicator of lymph node metastasis in NPC. In the endemic areas of China, positive EBV accounts for the vast majority 8,14,15 . Of interest though, in our available data, most patients with NPC had a negative EBV result.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…EBV is a particularly sensitive indicator of lymph node metastasis in NPC. In the endemic areas of China, positive EBV accounts for the vast majority 8,14,15 . Of interest though, in our available data, most patients with NPC had a negative EBV result.…”
Section: Discussionmentioning
confidence: 75%
“…In the endemic areas of China, positive EBV accounts for the vast majority. 8,14,15 Of interest though, in our available data, most patients with NPC had a negative EBV result. It has been reported in numerous studies that the incidence of EBV-associated NPC appears to be related geographically 1,15,16 .…”
Section: Discussionmentioning
confidence: 83%
“…Previously reported studies confirmed that EBV DNA level before, during and after treatment all are significant predictors of clinical outcomes in NPC patients 16‐20 . But the clinical features and prognostic value of consistently negative EBV DNA status have rarely been studied.…”
Section: Discussionmentioning
confidence: 98%
“…Currently, anti-NPC regimens are adopted according to the sites of tumor invasion and TNM staging. However, tumor heterogeneity also affects the efficacy among patients at this stage ( 37 ). In addition, there are a number of studies on the prognostic value of plasma EBV-DNA levels in NPC.…”
Section: Discussionmentioning
confidence: 99%